Carcass Evaluation of Crossbred Betweeen Cockerel Kampung Chicken and Layer Hen - Muryanto, Muryanto; PS, Hardjosworo; R, Herman; H, Setijanto (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2002)
The research was conducted to the characteristics of carcass evaluate crossbred between cockerel of kampung chicken and Lohman layer hen. Sixteen crossbred chickens and 16 kampung chickens were reared under a similar management from 2 - 12 weeks old. The chickens were given a commercial feed which contains 21% crude protein at 2 - 4 week old, and 14% crude protein and metabolizable energy 2800 kcal/kg at 4 - 12 weeks old. The data of carcass weight, rear back weight, fore back weight, breast weight, and thigh weight were collected. Meat and bone on breast and thigh were separated. The results showed that with under similar management and feeding, the carcass values of crossbred chicken were not significantly different with kampung chicken. The crossbred chickens have meat production rate of 2.83 times as compared to kampung chicken. Higher crude protein than 14% with a balance metabolizable energy will increase the quantity and quality of crossbred chicken carcass. (Animal Production 4(2): 71-76 (2002)Â Key Words : Carcass, Crossbred Kampung Chicken